PEMODELAN KURS DOLLAR AMERIKA SERIKAT TERHADAP RUPIAH MENGGUNAKAN REGRESI PENALIZED SPLINE DILENGKAPI GUI R - Gina Wangsih; Suparti Suparti; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
United States Dollar (USD) exchange rate movement against Rupiah is the main guideline for economic actors in making decisions. Exchange rate movement of USD against Rupiah is a time series data. One of the statistical methods that can be used for modelling time series data is ARIMA. ARIMA method data must be stationery and residuals must be normally distributed, independent, and constant variance, which means an alternative model is needed so that it is not bound by any assumptions, namely a nonparametric penalized spline regression model. Selling rate data of USD against Rupiah is modeled using nonparametric penalized spline regression because the assumptions in the ARIMA model are not fulfilled. Penalized spline regression modeling is using full search algorithm in determining knot points. Lambda values are tested from 0 to 100000 on order 2, 3, and 4. Optimal penalized spline model is a model with minimum GCV value. R GUI facilitate the process of selecting the best model. Data is divided into 2 parts, namely in sample data for model formation and out sample data for evaluating the best model performance based on MAPE value. Penalized spline regression modeling produces the best model, namely optimal penalized spline model with minimum GCV value achieved on 3rd order with 35 knot points and lambda value = 2007. 96,20% value of R Squared model indicates the model is a strong model. In the evaluation of the best model, the MAPE data out sample value is 0.65%. MAPE value indicates the model has very good forecasting ability.